2014
DOI: 10.1080/00918369.2014.977115
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Perspective of the Relational Processes for Family and Individual Development During the Mediation of Religious and Sexual Identity Disclosure

Abstract: Although the psychological literature regarding gay men from religious families is continually expanding, it is also limited in that few studies focus on the use of therapy in the negotiation of the interrelated systems of religion, sexuality, and family. Utilizing a cultural historical activity theory-based process of analysis, this study focuses on the narratives of 12 clinicians discussing 230 conflicts and how those conflicts are mediated in both productive (e.g., seeking secular support) and unproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Similarly, Christian parents reported using God/faith in arguments even though this often led to an increase in verbal aggression and stonewalling (Brelsford & Mahoney, 2009; Brelsford, 2011). Clinicians working with gay men have also reported the negative relational effects of “ religion being coopted by a parent or family member to serve an agenda [emphasis in the original]” (Etengoff & Daiute, in press). This study expands the current body of research by exploring multiple familial perspectives of both the adaptive and maladaptive ways in which religion is used to navigate conflicts between gay men of various religious orientations and their Christian and Jewish relatives.…”
Section: Research Contextmentioning
confidence: 85%
See 2 more Smart Citations
“…Similarly, Christian parents reported using God/faith in arguments even though this often led to an increase in verbal aggression and stonewalling (Brelsford & Mahoney, 2009; Brelsford, 2011). Clinicians working with gay men have also reported the negative relational effects of “ religion being coopted by a parent or family member to serve an agenda [emphasis in the original]” (Etengoff & Daiute, in press). This study expands the current body of research by exploring multiple familial perspectives of both the adaptive and maladaptive ways in which religion is used to navigate conflicts between gay men of various religious orientations and their Christian and Jewish relatives.…”
Section: Research Contextmentioning
confidence: 85%
“…In addition, clinicians may find it helpful to assist clients in envisioning mediational alternatives that could have been used such as the religious values of family and love. For example, a clinician participating in a related study suggested that religious leaders use the scriptural narrative that “God didn’t let Abraham kill Isaac” to focus on creating more inclusive families and communities (Etengoff & Daiute, in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LGBTQ individuals are often afraid to come out to their family because they are aware of the risk for disassociation. Etengoff and Daiute (2015) give insight into fears of disassociation: "The increasing relational distance strategy was discussed in the following contexts: religious families abandoning, disowning, and rejecting the adult-child" (p. 411). In drastic situations, LGBTQ members are kicked out of their houses and become homeless upon coming out.…”
Section: Resistance To Changementioning
confidence: 99%
“…Hurt feelings reveal themselves in different ways depending on the individual, though Leary and Springer (2001) suggest crying, acting aggressively, belittling, and looking for other relationship fulfillment are the most common reactions. In a study by Etengoff and Daiute (2015), parents of LGBTQ individuals "experienced guilt and community shame" when their child diverged from heteronormative behavior (p. 406). The family members may begin to analyze the behaviors of the LGBTQ individual more closely in an attempt to devalue their relationship or control their behavior.…”
Section: Resistance To Changementioning
confidence: 99%